Faktor Yang Mempengaruhi Penggunaan Obat Kategori Over The Counter Pada Mahasiswa UNSIKA - Mally Ghinan Sholih; Indah Laily Hilmi; Rahmi Indian (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Survey conducted by the Statistics Indonesia in 2020 regarding self-medication, it was recorded that 88,28% people of West Java carried out self-medication, one of which was with over the counter drugs. The high use of this Over The Counter (OTC) category of drugs increases the possibility of abuse in terms of use. The purpose of this study is to identify the factors that influence the use of drugs in the OTC category and to test it againts Singaperbangsa Karawang University (UNSIKA) students. This research was conducted from January to March 2022 using a descriptive analytic design with a cross sectional approach. The instrument used is a questionnaire. The sampling technique used is the accidental sampling method with a sample consisting of 392 UNSIKA students who entered the inclusion criteria. The results of the univariate analysis shows that the majority of respondents have good knowledge, are influenced by product effectiveness and efficiency, have adequate information availability, believe in manufacturers, are influenced by usage preferences, and use drugs well. The results of the bivariate analysis using the Chi square method indicates that there is a relationship between knowledge, trust in manufacturers, and usage preferences for the use of drugs in the OTC category with a significance value of 0.001 (p <0.05) and there is no relationship between product effectiveness and efficiency and the availability of information on the use of drugs in the over the counter category with a significance value of 0.911 and 0.973, respectively (p > 0.05).